PERAN SHOPPING EMOTION DALAM MEMEDIASI PENGARUH ATMOSFER RITEL DAN PROMOSI TERHADAP IMPULSE BUYING - Diah Rani, Ni Putu Krisna; Purnami, Ni Made (E-Jurnal Manajemen; Vol 8 No 6 (2019), 2019)
The purpose of this study was to explain the influence of the retail atmosphere, and the promotion of emotions, to explain the influence of the retail atmosphere, promotion, and emotions on impulse buying, to explain the role of emotions as mediating the relationship between the retail atmosphere and promotion of impulse buying at Hypermart Mall Bali consumers. Galeria. The population in this study were all consumers who had shopped at Hypermart Mall Bali Galeria and had done Impulse Buying. The sampling method used was purposive sampling. The samples selected in this study were 108 respondents. Data were analyzed using path analysis techniques. Based on the results of the study shows that the retail atmosphere, and promotion has a positive effect on emotions. Retail atmosphere, promotion, and emotions have a positive effect on impulse buying. Emotions mediate the relationship between the retail atmosphere and promotion of impulse buying on Hypermart Mall Bali Galeria consumers. Keywords: retail atmosphere, promotion, emotion, impulse buying